2015
DOI: 10.1007/s10562-015-1579-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dispersion of the Active Phase on the Activity and Coke Formation over WO3/SiO2 Catalysts in the Metathesis of Ethylene and 2-Butene

Abstract: WO 3 /SiO 2 catalysts with various tungsten loadings were prepared by the incipient wetness impregnation method and studied in the metathesis of ethylene and trans-2-butene as feed to produce propylene. Two different calcination methods were used to modify the dispersion of the tungsten active phase. The catalysts were characterized by X-ray diffraction, transmission electron microscopy, nitrogen physisorption, ion-exchange titration, FT-Raman, ammonia temperature programmed desorption and temperature programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Many researchers mentioned that higher dispersion of tungsten on the support exhibited high activity of the metathesis reaction. 14,25,35 Additionally, the UV-Vis and Raman results also indicated the higher amount of isolated tetrahedral tungsten oxide and octahedral polytungstate species which were active species for the metathesis reaction 32 on the non-calcined catalysts than the calcined catalysts. The NH 3 -TPD and H 2 -TPR results also showed the higher degrees of metal-support of the non-calcined catalysts due probably to the strong acidity presented on the non-calcined ones.…”
Section: Resultsmentioning
confidence: 93%
“…Many researchers mentioned that higher dispersion of tungsten on the support exhibited high activity of the metathesis reaction. 14,25,35 Additionally, the UV-Vis and Raman results also indicated the higher amount of isolated tetrahedral tungsten oxide and octahedral polytungstate species which were active species for the metathesis reaction 32 on the non-calcined catalysts than the calcined catalysts. The NH 3 -TPD and H 2 -TPR results also showed the higher degrees of metal-support of the non-calcined catalysts due probably to the strong acidity presented on the non-calcined ones.…”
Section: Resultsmentioning
confidence: 93%
“…1 and S2b †) due to It was shown that a lower calcination ramp rate could enhance the catalyst activity in metathesis reaction from ethylene and 2butene as compared to the ones calcined with a higher rate because they led to better dispersed catalysts. 47 And the WO 3 crystals were also clearly detected in XRD at a high calcination temperature. 48 In our study, the speculated transformation of W phase is well conrmed by their UV-vis DRS spectra as shown in Fig.…”
Section: Effect Of Support Charactermentioning
confidence: 90%
“…Considering the dispersion of tungsten on the silica support (as conrmed by XRD and TEM results), it was found that the H 2 -treated non-calcined catalysts exhibited the activity higher than the H 2 -treated calcined catalysts, and the pretreatment temperature at 650 C of the H 2 -treated noncalcined catalyst showed the highest activity, indicating that better dispersion of tungsten on the silica support exhibited the high activity of metathesis of ethylene and 2-butene to produce propylene. 14,26,38 Moreover, the TEM mapping results also conrmed that the H 2 -treated calcined catalysts showed the more tungsten agglomerates dispersed on the surface silica support than the H 2 -treated non-calcined catalysts, indicating poor tungsten dispersion on the support. Additionally, the UVVis and Raman results indicated that the higher amount of isolated tetrahedral tungsten oxide was active species for metathesis reaction.…”
Section: Structural-activity Relationshipmentioning
confidence: 84%
“…In addition, small crystal size of these phases also exhibited the high catalytic activity, which was related with higher tungsten dispersion on the support. 14,26 Therefore, the two mentioned crystalline phases are good proxy (indicators) of the reducibility of the W oxide phase, which itself is related to dispersion.…”
Section: Resultsmentioning
confidence: 99%